2019
DOI: 10.1136/injuryprev-2018-043025
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the speed limit from 30 mph to 25 mph in Boston: effects on vehicle speeds

Abstract: IntroductionEffective 9 January 2017, the default speed limit on Boston streets was reduced from 30 mph to 25 mph. This study evaluated the effects of the speed limit reduction on speeds in Boston.MethodVehicle speeds were collected at sites in Boston where the speed limit was lowered, and at control sites in Providence, Rhode Island, where the speed limit remained unchanged, before and after the speed limit change in Boston. A log-linear regression model estimated the change in vehicle speeds associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Therefore, "regression-to-the-mean" is an unlikely explanation for the effect noted. The effectiveness of posted speed limit reduction on PMVC risk and PMVC injury severity found in this study is similar to previously reported studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, "regression-to-the-mean" is an unlikely explanation for the effect noted. The effectiveness of posted speed limit reduction on PMVC risk and PMVC injury severity found in this study is similar to previously reported studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Twenty miles per hour (32 km/hour) or 30 km/hour speed limits represent a potential strategy to reduce urban road injuries and are becoming increasingly widespread in Western countries 1–3. This is because reducing road injuries is a priority for public health; as such, injuries are among the leading causes of death and disability worldwide, with more than one million individuals dying each year on the road 4.…”
Section: Introductionmentioning
confidence: 99%
“…a. Using freely available data repositories such as UCI, 3 Kdnuggets, 4 and SNAP. 5 b. Twitter Premium Application Programming Interface (API): Twitter provides multiple packages for APIs to collect tweets within a 30-day span or the full archive duration, where tweets starting from 2006 can be collected based on a set of query keywords.…”
Section: Data Source and Collectionmentioning
confidence: 99%
“…With more than one million individuals dying each year on the road [1], reducing road casualties is a public health priority. Twenty miles per hour (20mph) speed limit policies (equivalent to roughly 30kmh) have become a part of public health policies to reduce urban road collisions and casualties, especially in Western countries [2,3]. Twenty mph limits are predominantly sign-based measures to reduce motor vehicle speed and are mainly used in residential areas.…”
Section: Introductionmentioning
confidence: 99%